Evaluación de la eficiencia de un piloto de fitorremediación multiproceso en el tratamiento de suelos contaminados con residuos del Campo Rubiales bajo el marco regulatorio Louisiana 29B (2021)
The objective of this research project was to carry out a multiprocess phytoremediation pilot in the treatment plant of the company AW Company S.A.S. Yopal, seeking fast and sustainable means of remediation due to its complementary processes favoring plant growth and the development of the microbial community by reducing polluting and environmental stress, increasing the effective degradation of TPH oils and fats due to the abundance of roots and microbial biomass obtaining high remediation rates within acceptable time frames. For such purposes, the following working hypothesis was proposed: By implementing a multiprocess phytoremediation pilot, compliance with the safe concentrations of the following physicochemical parameters will be guaranteed: pH, conductivity, humidity, total nitrogen, total phosphorus, TPH, arsenic, barium, cadmium, chromium + 6, lead, zinc, mercury, selenium, potassium, RAS and ESP; contemplated in Louisiana Standard 29B.